1987
DOI: 10.1021/bi00392a017
|View full text |Cite
|
Sign up to set email alerts
|

Purification and amino acid sequence of chicken liver cathepsin L

Abstract: Cathepsin L was purified from chicken liver lysosomes by a two-step procedure. Cathepsin L exhibited a single band of Mr 27,000 by sodium dodecyl sulfate-polyacrylamide gel electrophoresis under reducing conditions, presented a high affinity for the substrate Z-Phe-Arg-NMec, was very unstable at neutral pH, and was inhibited by Z-Phe-Phe-CHN2. The complete amino acid sequence of cathepsin L has been determined and consists of 215 residues. The sequence was deduced from analysis of peptides generated by enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…11 ,12,28) Wad a and Tanabe 27 ) purified a dimer form of cathepsin L from chicken liver using a sophisticated procedure. However, Dufour et al 20 ) purified a single chain form (monomer) Table II using a relatively rapid procedure. The same phenomena were also observed in the purification of sheep liver cathepsin L. 15 ,28) In this study, the monomer form of mackerel cathepsin L was similar to that of human liver,29) chicken liver,20) and salmon muscle 16 ) cathepsinL.…”
Section: Molecular Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…11 ,12,28) Wad a and Tanabe 27 ) purified a dimer form of cathepsin L from chicken liver using a sophisticated procedure. However, Dufour et al 20 ) purified a single chain form (monomer) Table II using a relatively rapid procedure. The same phenomena were also observed in the purification of sheep liver cathepsin L. 15 ,28) In this study, the monomer form of mackerel cathepsin L was similar to that of human liver,29) chicken liver,20) and salmon muscle 16 ) cathepsinL.…”
Section: Molecular Weightmentioning
confidence: 99%
“…Among these reductants, 1 mM of cysteine and DTT were enough to completely activate the enzyme activity. According to Dufour et al,20) the cathepsin L obtained from chicken liver was activated by 2 mM DTT, while that from salmon required both f3-Me and DTT for activation. 16) These phenomena suggest that the formation of disulfide bonds is important in the denaturation of the unique conformation that maintains the proper function of these proteinases.…”
Section: Effects Of Reductantsmentioning
confidence: 99%
“…Cathepsin L exists in the two-chain form in mouse peritoneal macrophages but not in the macrophage-like mouse WEHI-3 cell line [76]. Chicken liver cathepsin L is primarily a single-chain enzyme [36]. Tang and coworkers [26] found that bovine cathepsin D contains about 68% of the single-chain species, whereas the porcine kidney enzyme contains only 5%.…”
Section: Light-heavy Chain Cleavagementioning
confidence: 99%
“…The N-terminal sequence of the 30-kDa protease was compared to the N-terminal sequence of F. hepatica-1 cathepsin L (4), F. hepatica-2 cathepsin L (5), chicken liver cathepsin L (14), rat liver cathepsin L (15), human liver cathepsin L (16), and bovine liver cathepsin L (17). (6).…”
Section: Discussionmentioning
confidence: 99%